Cost-Efficiency Analysis of the Improved Web-Based Planning, Budgeting, and Reporting System (PlanRep) in Tanzania - Ruhago, George M.; Kapologwe, Ntuli A.; Ngalesoni, Frida N.; Kengia, James T.; Kibusi, Stephen M.; Kalolo, Albino; Kitali, Erick J.; Mtatifikolo, James D.; Masuha, Sutte R.; Kikula, Amani; Mtei, Gemini (Frontiers in Health Services, 2022)
Background Information systems offer unlimited potential for innovation and digitalization of management functions to facilitate citizen participation and improve accountability, transparency, and efficiency in government operations and service delivery. In line with this, for more than one decade, Tanzania implemented an integrated planning, budgeting, and reporting system (PlanRep) that was used to prepare plans and budgets at the local government authorities (LGAs) using a desktop application. In 2017, PlanRep was upgraded to a Web-based system to address several challenges, including poor coordination and high cost involved in the preparation of plans and budgets. However, operational evidence regarding the cost-efficiencies and benefits of shifting to Web-based PlanRep has not been explored. This study aims to address this gap by assessing efficiency gains (in terms of cost and time) of shifting to a Web-based PlanRep system as a tool for the preparation of LGA plans and budgets. Methods The study applied a retrospective before-and-after study design whereby quantitative data was used to assess the amount of time and the cost incurred by LGAs when preparing their budget 1 year before the introduction of PlanRep and 1 year after. Parallelly, qualitative data were collected through key informant interviews with selected LGA officials, Regional Secretariats (RSs), President's Office Regional Administration and Local Government (PORALG), and system end-users such as heads of health facilities and schools (primary and secondary). Secondary data was analyzed by comparing time and cost used before and after Web-based PlanRep, while thematic analysis was employed for qualitative data. Results The analysis showed a 53% reduction (from USD 3.8 million in 2017/18 to USD 1.8 million in 2018/19) in the total costs LGAs incurred during planning and budgeting after introducing the Web-based PlanRep. The main efficiency gain was related to per diem costs. The analysis also showed significant time saving from an average of 87 days in 2017/18 to only 8 days in 2018/19. PlanRep system end-users also acknowledged that the introduction of Web-based PlanRep has significantly saved their time and costs in preparation of LGA plans and budget. Conclusion The introduction of the Web-based planning, budgeting, and reporting systems has resulted in tremendous cost reduction, time savings, transparency, accountability, and workload reduction. The findings offer operational evidence to guide the implementation and scale up of similar systems in countries that share equivalent circumstances like Tanzania.